Inspired by Abhiram Rao

Algebra Level 3

2015 a 2015 = 2016 a 2016 \large 2015a_{2015} = 2016a_{2016}

In a non-constant arithmetic progression , the 2015 times the 2015 th {2015}^{\text{th}} term is equal to 2016 times the 2016 th {2016}^{\text{th}} term. Which term of this arithmetic progression is 0?


Inspiration .


The answer is 4031.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

5 solutions

Ashish Menon
May 24, 2016

2015 a 2015 = 2016 a 2016 2015 ( a + 2014 d ) = 2016 ( a + 2015 d ) 2015 a + 2015 × 2014 d = 2016 a + 2015 × 2016 d 2015 a 2016 a = 2015 × 2016 d 2015 × 2014 d a = 2015 d ( 2016 2014 ) a = 4030 d 2015 a_{2015} = 2016 a_{2016}\\ 2015(a + 2014d) = 2016(a + 2015d)\\ 2015a + 2015 × 2014d = 2016a + 2015 × 2016d\\ 2015a - 2016a = 2015 × 2016d - 2015 × 2014d\\ -a = 2015d(2016 - 2014)\\ a = -4030d

Let the nth term in the AP be 0 0 . Then a + ( n 1 ) d = 0 a = ( n 1 ) d 4030 d = ( n 1 ) d 4030 = ( n 1 ) n = 4031 a + (n-1)d = 0\\ \implies a = -(n-1)d\\ \implies -4030d = -(n-1)d\\ 4030 = (n-1)\\ \implies n = \color{#69047E}{\boxed{4031}} .


Generalizing:-
Let n n times a n a_n = m m times a m a_m .
Then n ( a + ( n 1 ) d ) = m ( a + ( m 1 ) d ) n ( a + d n d ) = m ( a + d m d ) a n + d n 2 d n = a m + d m 2 d m a n a m + d n 2 d m 2 d n + d m = 0 a ( n m ) + d ( n 2 m 2 n + m ) = 0 a ( n m ) + d ( n 2 m 2 ( n m ) ) = 0 a ( n m ) + d ( ( n m ) ( n + m 1 ) ) = 0 ( n m ) ( a + ( n + m 1 ) d ) = 0 a + ( n + m 1 ) d = 0 a n + m = 0 n(a + (n - 1)d) = m(a + (m - 1)d)\\ n(a + dn - d) = m(a + dm - d)\\ an + dn^2 - dn = am + dm^2 - dm\\ an - am + dn^2 - dm^2 - dn + dm = 0\\ a(n - m) + d\left(n^2 - m^2 - n + m\right) = 0\\ a(n - m) + d\left(n^2 - m^2 - (n - m)\right) = 0\\ a(n - m) + d\left(\left(n - m\right)\left(n + m - 1\right)\right) = 0\\ (n - m)\left(a + (n + m - 1)d\right) = 0\\ a + (n + m - 1)d = 0\\ a_{n + m} = 0

So, if ever, n times nth term is equal to m times mth term of a non-constant arithmetic progression, then the (m + n)th term is 0 0 .

Did the same way! :D

Arkajyoti Banerjee - 5 years ago

Log in to reply

Nice! :) :)

Ashish Menon - 5 years ago

Nice problem bro! (+ 1)upvoted!

It can be generalized(after proving) as follows:-

" If N times the N'th term is equal to M times the M'th term of a non-constant arithmetic progression , Then its (M+N) 'th term will be equal to zero. "

THANK YOU.

Rishabh Tiwari - 5 years ago

Log in to reply

Yes it is perfect! Thanks!

Ashish Menon - 5 years ago

Log in to reply

Are u in 11th standard presently?

Rishabh Tiwari - 5 years ago

Log in to reply

@Rishabh Tiwari Yes but it will start after vacations.

Ashish Menon - 5 years ago

Log in to reply

@Ashish Menon Ok mine 2 .! Have u joined any coaching!?

Rishabh Tiwari - 5 years ago

Log in to reply

@Rishabh Tiwari I have school and coaching at the same centre :- Edunova

Ashish Menon - 5 years ago

Log in to reply

@Ashish Menon Oh thats gr8 ! Btw ur brilliant. .all your lev5 and mastery in subjects which haven't been taught yet !! Can you plz help me that how can I know which problem to be posted?? So that they get rated in community?

Rishabh Tiwari - 5 years ago

@Ashish Menon All of my ques. Are left unrated !! I have posted like 7-8 questions...

Rishabh Tiwari - 5 years ago

I generalized it in my solution.

Ashish Menon - 5 years ago

Log in to reply

Its perfect now!

Rishabh Tiwari - 5 years ago

I simply assume that the one will be 2016 and another will be 2015, and then by mental calculation, I understand that the common difference between terms is one, and hence I understand that the answer is (2015+2016/1)=4031

Log in to reply

Thats nice. Not a formal answer but can be used to find answer quickly.

Ashish Menon - 5 years ago
Abc Xyz
May 25, 2016

2015 a 2015 = 2016 a 2016 2015a_{2015} = 2016a_{2016}

2015 a 2015 = 2016 ( a 2015 + d ) 2015a_{2015} = 2016(a_{2015} + d) .....................................Let d be the common difference. So obviously a 2016 = a 2015 + d a_{2016}=a_{2015} + d

2015 a 2015 = 2016 a 2015 + 2016 d 2015a_{2015}=2016a_{2015} + 2016d

2016 a 2015 2015 a 2015 + 2016 d = 0 2016a_{2015} - 2015a_{2015} + 2016d = 0

a 2015 + 2016 d = 0 a_{2015} + 2016d = 0

So clearly when you add common difference 2016 times you will get a 2015 + 2016 a_{2015 + 2016}

Which is a 4031 a_{4031} ............. 4031 st term in the series

Therefore the answer is 4031 \boxed{4031}

Chew-Seong Cheong
May 27, 2016

2016 a 2016 = 2015 a 2015 2016 a 2016 2015 a 2015 = 0 a 2016 + 2015 ( a 2016 a 2015 ) = 0 a 2016 + 2015 d = 0 d = common difference a 4031 = 0 2016 + 2015 = 4031 \begin{aligned} 2016a_{2016} & = 2015a_{2015} \\ 2016a_{2016} - 2015a_{2015} & = 0 \\ a_{2016} + 2015(\color{#3D99F6}{a_{2016} - a_{2015}}) & = 0 \\ a_{2016} + 2015\color{#3D99F6}{d} & = 0 \quad \quad \small \color{#3D99F6}{d = \text{common difference}} \\ \implies \boxed{a_{\color{#3D99F6}{4031}}} & = 0 \quad \quad \small \color{#3D99F6}{2016+2015=4031} \end{aligned}

The 4031 \boxed{4031} th term is equal to 0.

Pranay Agrawal
May 25, 2016

I have done tuhis by the same. Thanks for the solution.

Thanks! :) :)

Ashish Menon - 5 years ago
David Castillo
May 24, 2016

Let c c be the common difference and a n a_n the term which is zero. Then 2015 a 2015 = 2016 ( a 2015 + c ) 2015a_{2015} = 2016(a_{2015}+c) and a 2015 + 2016 c = 0 = a n a_{2015} + 2016c = 0 = a_n . Given that in an arithmetic progression the n t h n^{th} therm can be expressed as a n = a k + ( n k ) c a_n = a_k + (n-k)c , we have that 2016 = n 2015 2016 = n-2015 and therefore n = 4031 n = 4031 .

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...